Dihydroartemisinin decreases pre-existing neutralizing antibodies against adeno-associated virus in challenged mice - Fang, Jingjing; Cui, Enze; Xie, Jinyan; Gao, Xuxia; He, Yun; Yang, Ming; Shaheen, Sana; Zhou, Zhengjun; Zhou, Shaolai; Cheng, Binbin; Ling, Changquan; Ling, Chen (Frontiers in Pharmacology, 2025)
IntroductionThe high prevalence of pre-existing neutralizing antibodies (NAbs) against adeno-associated virus (AAV) poses a major obstacle to in vivo gene therapy. Current immunosuppressive (IS) strategies, such as corticosteroids, are limited by toxicity and adverse effects. To explore safer alternatives, we evaluated dihydroartemisinin (DHA), a synthetic derivative of artemisinin inspired by traditional Chinese medicine (TCM), as a potential IS agent.MethodsIn vivo experiments were conducted by administering DHA at either 30 or 210 days post-injection (PI) of rAAVDJ vectors. Anti-AAV NAb levels, transgene expression, and vector genome biodistribution were assessed. Flow cytometry was used to quantify CD20+ B cells, germinal center B cells, and plasma cells in the spleen. Splenic gene expression profiling, liver histology, and serum biochemical analyses were performed to evaluate immunological and safety responses. In vitro, the impact of DHA and its serum metabolites on rAAV infection efficiency was tested in HEK293 cells.ResultsDHA administration significantly reduced anti-AAV NAb levels without compromising transgene expression or vector genome distribution. DHA treatment resulted in a reduction of splenic CD20+ B cells, germinal center B cells, and plasma cells, alongside changes in splenic gene expression profiles. Liver histology and serum markers confirmed that DHA at 125 mg/kg/day did not induce hepatotoxicity. In vitro assays demonstrated that DHA and its blood metabolites did not interfere with rAAV infection of HEK293 cells across multiple serotypes.DiscussionThese findings suggest that DHA is a safe and effective agent for modulating humoral immune responses to AAV vectors. Our results provide proof-of-concept evidence supporting the use of TCM-derived compounds to address immunological barriers in gene therapy.